COVID-19 and global clothing retailers' responsibility to vulnerable workers: NGO counter-rhetoric. Issue 1 (26th August 2021) - Ahmad, Nglaa; Haque, Shamima; Islam, Muhammad Azizul
Abstract : Purpose: This article aims to examine how non-governmental organisations (NGOs)' narratives portray the vulnerability of workers in global clothing supply chains during the COVID-19 crisis. Design/methodology/approach: The research analyses the rhetoric in global clothing retailers' and NGOs' counter-rhetoric during the first seven months of 2020. Findings: During this period, retailers employed rhetorical strategies to legitimise irresponsible actions (corporate hegemony prevailed), while NGOs embraced forms of counter-rhetoric trying to delegitimise the retailers' logic, stressing the role of neoliberalism in worsening the situation. Originality/value: The authors contribute to the literature by providing new insight into the consequences of COVID-19 for retailers' neoliberal practices and the livelihood of workers in global supply chains. Findings of this study extend authors' knowledge about retailers' COVID-19 measures: These have contributed to the plights of workers working for their supply factories in the global South.